The aberrant levels of decorin induce damages of human salivary gland epithelial cells and polarization of macrophages. Issue 3 (19th April 2022) - Gao, Rongfen; Tang, Jungen; Dong, Yuanji; Ming, Bingxia; Yu, Zhihua; Zhong, Jixin; Dong, Lingli
ABSTRACT: Objectives: This study aimed to preliminarily address the levels of decorin (DCN, a critical component of extracellular matrix) and its potential roles in primary Sjögren's syndrome (pSS). Methods: DCN levels were determined in the salivary glands of experimental SS (ESS) mice and pSS patients by RNA sequencing, bioinformatics analysis, or immunohistochemical staining. Its correlation with interested genes and co-localization with a putative receptor was studied in pSS patients. In addition, its potential roles on salivary gland epithelium and macrophages were tested by exogenous administration to corresponding cell lines, followed by the evaluation of apoptosis using flow cytometry or cytokine expression using quantitative real-time polymerase chain reaction. Results: Our data revealed a significant elevation of DCN in the salivary glands of the ESS mice model and pSS patients. In addition, the bioinformatics analysis of DCN in the GSE40611 (RNA-seq, parotid glands) dataset displayed an elevation of the DCN level in the parotid glands of pSS patients that positively correlated with several chemokines ( CXCL13, CXCL9, and CCL20 ), Interleukin -1 β (IL1 -β), and caspase3 but negatively correlated with the proliferation relative gene MKI67. The stimulatory effects of DCN on the salivary gland epithelial cells (A253 cell line) and macrophages have been determined as they are considered active participants in the progression of SS. The data showed that DCN induced the apoptosis of A253 cells and polarization of macrophages towards the M1 phenotype, characterized by the expression of pro-inflammatory cytokines. Conclusions: Our study provided preliminary evidence to understand the clinical significance of DCN in pSS and broadened our horizons in understanding the mechanism of pSS.